Implementation of P5 in Schools for Student Development: A Literature Review - Naufal Roif Syahli; Egner Bernard Pribadi; Puja; Gian Devina Gracia Nehe; Yesica Natalia Simangunsong; Cindy Natalie Rumahombar; Melly Br Bangun (International Journal of Educational Practice and Policy, 2024)
This study investigates the implementation of the Pancasila Learner Profile in the Merdeka Curriculum in terms of its contribution to the character and competency development of the students. This study looks at how the Pancasila Learner Profile (P5) is used in the Merdeka Curriculum and how it helps students become more competent and morally upright. This study assesses the literature on P5 implementation in schools using the literature review approach. According to the findings, P5 contributes significantly to the development of critical thinking abilities, creativity, teamwork, and moral principles via a student-centered, contextual, and multidisciplinary approach. Among the difficulties noted are resource availability, community participation, and teacher preparedness. Among the suggestions include enhancing teacher preparation programs, providing facilities for assistance, and creating locally relevant initiatives.